Alternative method for predictive functional control to handle an integrating process - Abdullah, Muhammad; Rossiter, John Anthony (IEEE, 2018)
This work proposes an improved method for Predictive Functional Control (PFC) to handle an integrating process. Instead of assuming a constant future input, the dynamic is shaped with a first-order Laguerre polynomial so that it converges to the expected steady state value. This modification provides simpler coding and tuning compared to the conventional method in the literature. Simulation results show that the proposed controller improves the consistency of the open-loop prediction of an integrating process and thus improves closed-loop performance and constraint handling properties. The practicality of this algorithm is also validated on laboratory hardware.